Oxidative stress in lung cancer patients is associated with altered serum markers of lipid metabolism. - Katarzyna Zabłocka-Słowińska; Sylwia Płaczkowska; Katarzyna Skórska; Anna Prescha; Konrad Pawełczyk; Irena Porębska; Monika Kosacka; Halina Grajeta (PLoS ONE, 2019)
In lung cancer (LC), alterations in redox balance are extensively observed and are a consequence of disease as well as co-occurrent with smoking. We previously demonstrated that metabolic disturbances such as trace element status and carbohydrate metabolism alterations are linked with redox status. The aim of this study was to evaluate relationships between the serum parameters of lipid metabolism and redox balance in LC patients. Serum parameters of lipid metabolism, i.e. total cholesterol (T-C), HDL cholesterol (HDL-C), LDL cholesterol (LDL-C), triglycerides (TG), T-C:HDL-C ratio, non-HDL-C, apolipoprotein A1 (Apo-A1), apolipoprotein B (Apo-B) and Apo-B:Apo-A1 ratio, as well as systemic redox status, i.e. total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), vitamin E (VE), vitamin C (VC), malonyldialdehyde (MDA), conjugated dienes (CD), and 4-hydroxynonenal (4-HNE) were determined in 92 LC patients and 82 control subjects (CS). LC women had significantly lower T-C and LDL-C, and higher TG, while HDL-C, Apo-A1 and Apo-B were significantly decreased in LC patients regardless of sex, when compared to CS. LC men had alterations in the systemic total redox balance such as lower TAS and higher OSI than CS men. LC women had lower VC, but VE was decreased in LC patients, regardless of sex. We observed higher lipid peroxidation in LC patients expressed via higher 4-HNE and CD. Systemic redox disturbances were associated with serum lipid alterations: TOS and OSI were positively correlated with T-C:HDL-C ratio and Apo-B:Apo-A1 ratio and negatively with HDL-C. The parameters of lipid peroxidation CD and MDA were significantly associated with variables reflecting lipid disturbances. The observed correlations were strengthened by general overweight/obesity, abdominal obesity, hypertriglyceridemia and non-smoking status. In conclusion, parameters related to lipid alterations are associated with oxidative stress in LC patients. The largest contribution from lipid parameters was revealed for T-C:HDL-C ratio, HDL-C and Apo-B:Apo-A1 ratio, while the largest contribution from redox status was revealed for OSI and VE. Overweight, obesity, hypertriglyceridemia and non-smoking status intensified these relationships.